Evaluation of the progression and treatment of experimental periodontitis in rats subjected to chemotherapy with 5-fluorouracil - Garcia, Valdir Gouveia [UNESP]; Noronha Novaes, Vivian Cristina [UNESP]; Almeida, Juliano Milanezi de [UNESP]; Longo, Mariellen [UNESP]; Ervolino, Edilson [UNESP]; Mogami Bomfim, Suely Regina [UNESP]; Theodoro, Letícia Helena [UNESP] (Springer, 2015)
This study aimed to evaluate the progression and treatment of experimental periodontitis (EP) in rats treated with 5-fluorouracil (5-FU).One-hundred fifty rats were divided into groups: C-control, EP-EP induction, EP/scaling and root planing (SRP)-EP induction and SRP, 5-FU-systemic treatment with 5-FU, 5-FU/EP-systemic treatment with 5-FU and EP induction, and 5-FU/EP/SRP-systemic treatment with 5-FU, EP induction and SRP. Systemic treatment consisted of the administration of 80 and 40 mg/kg of 5-FU. The animals were euthanised at 7, 15 and 30 days. Histological and immunohistochemical analyses for the detection of the receptor activator of nuclear factor-kappa B ligand (RANKL), osteoprotegerin (OPG) and tartrate-resistant acid phosphatase (TRAP) were performed at the furcation region. A histometric analysis was performed to evaluate the percentage of bone in the furcation region (PBF).In the 5-FU/EP and 5-FU/EP/SRP groups, there was less PBF, greater breakdown of periodontal tissues and increased immunostaining for RANKL compared with the EP and EP/SRP groups.It can be concluded that 5-FU aggravates PE progression, impairs the host response to SRP mechanical therapy and does not seem to cause changes in the healthy periodontium.
Keywords: Periodontitis; Rats; Bone resorption; Antineoplastic agents; Fluorouracil